Model of dependence of estimation of abrasive material wear-resistance from loading and density - Вишневський, О.А. (Proceedings of National Aviation University (archive), 2004)
In the given work the model of dependence of estimation of size of a sample surface abrasive interaction and particles from loading and density is specified. Modelling is made in view of average pressure upon a surface of contact of a sample and a rubber roller, density of a material and granularity of an abrasive.